Prevalence of Asthma in a Portuguese Countryside Town:Repercussions on Absenteeism and Self-Concept - Borrego, LM (2005)
Background: Childhood asthma represents an increasing health problem and is the leading cause of hospital admission and absenteeism in children with chronic disease. It also compromises quality of life, eventually contributing to disturbances in self-concept. Self-concept is a recent and global perspective of “the self” and relates to skills, self-image and self-esteem. Little information is available on this topic and there are no data from Portuguese countryside towns. Objective: The aim of this study was to determine the prevalence of asthma among all school children in the 5th and 6th grades in a Portuguese countryside town and to establish its possible correlation with absenteeism and self-concept. Methods: In April 2002, two questionnaires were administered in the presence of the researcher to a group of 950 children attending different schools. The children completed the internationally renowned questionnaires: ISAAC and the Self-Concept Scale by Susan Harter. Results: Our sample (n = 818) had a mean age of 11 years (10-15 years) and a male-to-female ratio of 1/1. The cumulative prevalence of asthma was11.9% and that of active asthma was 8.8 %; 63.9% of asthmatics were male and 36.1 % were female. The mean age of asthmatics was 11.34 years and 74 % had active symptoms. Comparison of this group of 97 asthmatic children with the remaining children revealed a statistically significant correlation between the presence of asthma and school absenteeism (global: p = 0.04; gymnastics: 0.05). Regarding the Self-Concept Scale a statistically significant association was found between the presence of asthma and school achievement (p = 0.027), physical appearance (p = 0.015), behavior (p < 0.000) and self-esteem (p < 0.000). No statistically significant correlations were found in social acceptance (p = 0.289) or athletic competence (p = 0.085). Asthmatic boys had higher self-concept scores than girls, except in the domain of behavior. Conclusions: Twelve percent of the population studied was asthmatic. In asthmatic children, absenteeism was higher and self-concept was lower for almost all domains, except social acceptance and athletic achievement, probably due to overprotection.